Waterlogging Simulation and Drainage Countermeasures of Aotou Yuanpan Area in Daya Bay Based on MIKE URBAN - TAN Yuxin; WU Duanwei (Renmin Zhujiang)
Under the multiple impacts of urbanization,extreme rainstorms,and tidal level,the waterlogging situation in coastal cities is severe.To effectively assess the risk of waterlogging in coastal cities and propose targeted waterlogging prevention and control strategies,this study employs MIKE URBAN to analyze the drainage capacity of the pipe network and simulate urban waterlogging in Aotou Yuanpan of Daya Bay.The results show that the design frequency of 86% current pipe network is less than once a year,and the total waterlogged area is 631 824 m2,with the water retention time exceeding 24 h in Aotou Yuanpan.Therefore,the waterlogging is caused by the low drainage standards of the pipe network and the riverway.The waterlogged water can be directly discharged to Danao River by setting up a 32 m3/s pumping station and building new culverts on Zhongxing Central Road,Beiao Road,and Jingang Road in the independent Yuanpan catchment area.Meanwhile,the total waterlogged area can be reduced to 5 248 m2,and the water depth and retention time can be lowered to less than 0.15 m and 0 h respectively,thus effectively alleviating the waterlogging in Aotou Yuanpan.This study provides a solution for the reconstruction of drainage facilities and the prevention and control of waterlogging disasters in Aotou Old Town,which carries certain reference significance for engineering projects of the same type.